Exploring the variability of Mexican EFL teachers’ ratings of high school students’ writing ability - González Quintero, Elsa Fernanda; Roux Rodríguez, Ruth (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
EFL teachers generally use scoring rubrics to assess students’ writing seeking to rate consistently and objectively so that assigned scores reflect students’ abilities rather than other unrelated factors. Research has found that raters’ judgment varies, depending on their linguistic, educational and professional/personal background. This study investigated the degree of difference among the scores of two Mexican raters of academic papers written in English as a foreign language by six high school students. Data came from two sources: 18 scored papers and raters’ comments during a semi structured interview. Results indicated that although the raters’ backgrounds were very similar, their judgments differed as a result of their personal perceptions of writing, scoring rubrics and writing assessment.